Integrasi Klorofil-a, SST, Dan Kedalaman Untuk Pemetaan Daerah Penangkapan Ikan Pelagis Kecil di Laut Jawa (Studi Kasus: WPPNRI 712) - Ades Suryaningtias; Ayang Armelita Rosalia; Kukuh Widiyanto (Universitas Nahdlatul Ulama Blitar, 2025)
The Fisheries Management Area of the Republic of Indonesia is divided into 11 regions, one of which is WPPNRI 712 or the Java Sea. One of the utilizations of these waters is the fishing zone. This study aims to map fishing zones in the Java Sea that can help improve the efficiency and success of fishing, as well as provide useful information for fisheries management. Several processes carried out in this study are collecting images, image cropping, extracting chlorophyll-a and SST data, interpolating using the IDW method, and overlaying. The high potential points for catching small pelagic fish in the Java Sea during the West Season are due to the high chlorophyll-a values and low sea surface temperatures (SST) which indicate an upwelling phenomenon. Transition Season I (March, April, May) is the peak season for catching small pelagic fish in the Java Sea. The potential for catching small pelagic fish is highest in March and April.